INDIVIDUAL COUNSELING SERVICES USING ASSERTIVE TECHNIQUES TO OVERCOME ANXIETY DISORDERS - Keyza Bella Aulia; Nina Nurhasanah; Cecep Taufiek Lazuardi; Amanda Khoerunnisa; Lusiyanawati Lusiyanawati; Syari Fitrah Rayaginansih (Psikoeduko: Jurnal Psikologi Edukasi dan Konseling, 2022)
Anxiety is a psychological disorder characterized by fear, concern about the future, prolonged worry, and nervousness. Anxiety is common for everyone, but it is called a psychological disorder when it prevents a person from living their daily life and carrying out productive activities. Anxiety disorders can occur in students in general Anxiety, academic Anxiety, and Social Anxiety. To deal with student anxiety disorders individually, counselors or supervising teachers can carry out individual counseling services. One technique of individual counseling services to deal with anxiety disorders is assertive training. Assertive training can help individuals who have difficulty expressing feelings be honest, transparent, and open but without harming, hurting, and offending other people so that they do not harbor their anxiety and can solve problems that cause anxiety.